2008
DOI: 10.1111/j.1937-8327.1993.tb00583.x
|View full text |Cite
|
Sign up to set email alerts
|

Instructional Designers Decisions and Priorities: A Survey of Design Practice

Abstract: For a number of years there has been a continuing debate on the degree to which instructional design models are used in practice. A study was conducted to determine if and how practicing course developers include instructional design activities in their projects. A survey was distributed to 73 practicing course developers who were asked to indicate how often they used eleven instructional design activities in their design projects and, as appropriate, to indicate why an activity was excluded from some projects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
78
1
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 98 publications
(83 citation statements)
references
References 6 publications
3
78
1
1
Order By: Relevance
“…Further corroborative support for the varying ways in which ID can be approached and executed is demonstrated by a number of classic empirical studies of variation in ID practice (Kirschner, van Merriënboer, Sloep, & Carr, 2002;Rowland, 1992; e.g. Tessmer & Wedman, 1992;Visscher-Voerman & Gustafson, 2004;Wedman & Tessmer, 1993).…”
mentioning
confidence: 96%
See 4 more Smart Citations
“…Further corroborative support for the varying ways in which ID can be approached and executed is demonstrated by a number of classic empirical studies of variation in ID practice (Kirschner, van Merriënboer, Sloep, & Carr, 2002;Rowland, 1992; e.g. Tessmer & Wedman, 1992;Visscher-Voerman & Gustafson, 2004;Wedman & Tessmer, 1993).…”
mentioning
confidence: 96%
“…Respectively, Tessmer and Wedman (1992), Wedman and Tessmer (1993), and Holcomb et al (1996) found it to be the least and second least frequently performed planning and analysis activity. While Winer, Vasquez-Abad, and Tessmer (1994) rank it near the middle, planning and analysis tied for the fifth least performed activity out of eleven total activities.…”
Section: Planning and Analysismentioning
confidence: 99%
See 3 more Smart Citations